Pain Caused by Ear Tagging in Kids of Native Black Goats - Zebaria, Hawar M.H.; Hidayet, Hoger M.; Al-Naqshabendy, Assel A. I.; Hussein, Nizar J.; Kakarash, Nawroz A. (Science Journal of University of Zakho, 2021)
There is no study about changes in behaviour and peripheral temperature of kid goats undergoing ear tagging procedure. This study was designed to elucidate that pain caused by ear tagging affects peripheral temperatures and behavioural observations in Karadi kid goats. Nineteen native black goat kids, aged 10 – 14 days, were used in this study. Eye and nasal temperatures were recorded before the ear tagging process, and after ear tagging 5 periods in 30 minutes. Besides, the researchers observed each kid’s behaviour for 30 minutes before ear tagging and 30 minutes after it, using focal sampling method and the data recorded with instantaneous time sampling to measure the duration and frequency of each behaviour of the kids. Results revealed that peripheral temperatures were significantly decreased for both eye (P≤0.01) and ear (P≤0.01) after ear tagging. The temperatures of both eye and ear decreased after tagging significantly (P≤0.01) for 30 minutes. The proportion of time kid goats spent normal standing and suckling the dam’s teat decreased whereas the proportion of time spent head-shaking increased after tagging. Significant differences were found between abnormal standing (P≤0.01) and vocalization (P≤0.01). It is concluded that ear tagging causes a considerable pain in kid goats and using surface temperatures and behaviour are useful indicators to approve it.